Tai textiles in the Mekong region continuity and change - Connors, Mary F. 1939- (Vietnam Museum of Ethnology, 2006)
Catalog of an exhibition that began at Vietnam Museum of Ethnology on Dec. 10, 2004, and opened at the Yunnan Nationalities Museum in Sept. 2006.